Pemaknaan Santri Terhadap Pembiasaan Bahasa Inggris dalam Majelis Alqur'an: (Studi Living Qur’an di Pondok Pesantren Hamalatul Qur’an Jombang) - Ahmad Fathurrobbani; Khoirul Huda; Muhammad Aufa Najah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study examines the interpretations of students' understanding of the practice of English language familiarization in the Al-Qur'an Assembly activities at the Hamalatul Qur'an Islamic Boarding School (PPHQ) in Jombang. This research uses a qualitative case study approach from a Living Qur'an perspective. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that the majority of students interpret the English language familiarization in the Al-Qur'an Assembly as a modern da'wah strategy that opens up opportunities for Islamic communication in the international sphere. This is in line with Surah Ar-Rum (30):22) concerning linguistic diversity as a sign of God's power, and is emphasized in Surah Ibrahim (14:4), Surah Az-Zukhruf (43:3), and Surah Fussilat (41:44) concerning the urgency of linguistic clarity in conveying revelation. Thus, the use of English in PPHQ is understood as an adaptive manifestation of Qur'anic values, uniting sacred traditions with the demands of the times. This study recommends the involvement of the Islamic boarding school community in supporting innovation to foster harmony between tradition and modernity. Keywords: Students, English, Al-Qur'an Assembly, Living Qur'an, Islamic Boarding School.